MSME Sustainability, E-Commerce, Capital Management: An Analysis of Islamic Perspective in the Context of the Digital Economy - Risnawati, Henny; Prakoso, Moedigdo Sigit; Jaelani, Achmad; Zabidi, Imron (International Journal of Marketing & Human Resource Research, 2025)
This study discusses the role of E-Commerce transactions and capital analysis in supporting micro, small, and medium enterprises (MSMEs) from an Islamic perspective. This study is qualitative with a descriptive approach, using triangulation as a data collection technique through observation, interviews, and documentation. This study focuses on culinary industry business actors in Segara Jaya Village, Bekasi City. The results of the study show that most respondents believe that the application of Islamic principles in capital and using the E-Commerce platform in business management is a good thing. This includes maintaining product quality, using halal-labeled raw materials, and prioritizing customer satisfaction. Respondents are committed to ensuring that every aspect of their business reflects the values and principles of Islamic teachings, making their business legally valid and based on Islamic ethics. These beliefs and practices positively impact the sustainability of their business. Furthermore, maximizing the potential of E-Commerce can help MSMEs adapt to the era of digital economic growth, thus providing opportunities for them to improve their business performance and sustainability in the digital world. Providing valuable guidance for entrepreneurs, governments, and related stakeholders. For culinary MSMEs, understanding that implementing E-Commerce is not a universal solution and the need for effective capital management can help in strategic decision-making. The government and MSME support institutions can utilize findings on the challenges of implementing E-Commerce to design more targeted support programs, including online marketing training and mentoring